(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2024)
In this study, it was aimed to evaluate the antioxidant and antimicrobial activities of Allium staticiforme bulb fractions (petroleum ether, chloroform, methanol and acetone) in vitro. Fractions were made by soxlet method, antibacterial activity was evaluated using disc diffusion method, antioxidant activity was evaluated using DPPH radical scavenging detection and reduction power test. At the same time, the chemical content was determined by examining TLC and total phenolic matter. The concentrations reducing the DPPH radical of the fractions by 50% were determined to be 283.1 μg/mL for methanol, 291.5 μg/mL for petroleum ether, 346 μg/mL for chloroform and 533.6 μg/mL for acetone, respectively. It was observed that the total phenolic substance amounts were in the order (from the higher to the lower): petroleum ether, methanol, chloroform and acetone fractions. The reduction power was directly proportional to the increase in the concentration for all fractions. The highest antibacterial effect was found on the petroleum ether fraction (12 mm) on S. aureus. It was determined that the petroleum ether fraction showed a broad spectrum of antibacterial activity. In the current study the antibacterial and the antioxidant activity of Allium staticiforme bulb fractions (with different polarity) have been investigated for the first time and shown that the solution used in extract preparation is important in revealing the bioactive molecules.